2015
DOI: 10.1016/j.neurobiolaging.2014.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Silencing phosphodiesterase 7B gene by lentiviral-shRNA interference attenuates neurodegeneration and motor deficits in hemiparkinsonian mice

Abstract: Different studies have suggested that the nucleotide cyclic adenosine 3', 5'-monophosphate can actively play an important role as a neuroprotective and anti-inflammatory agent after a brain injury. The phosphodiesterase 7 (PDE7) enzyme is one of the enzymes responsible for controlling specifically the intracellular levels of cyclic adenosine 3', 5'-monophosphate in the immune and central nervous systems. Therefore, this enzyme could play an important role in brain inflammation and neurodegeneration. In this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 53 publications
1
21
0
Order By: Relevance
“…Given the fact that alterations in the specialized niches of the adult brain underlay many different brain disorders including neurodegenerative disease, our work suggest that PDE inhibition could be a novel strategy for the treatment of these disorders. This idea is further substantiated by our previous work showing an important neuroprotective role of PDE7 inhibition in different brain disorders and by our previous report in which we demonstrated that PDE7 inhibition after S14 treatment in vivo induces a strong neurogenesis in the substantia nigra pars compacta of 6‐OHDA‐lesioned animals toward a dopaminergic phenotype .…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Given the fact that alterations in the specialized niches of the adult brain underlay many different brain disorders including neurodegenerative disease, our work suggest that PDE inhibition could be a novel strategy for the treatment of these disorders. This idea is further substantiated by our previous work showing an important neuroprotective role of PDE7 inhibition in different brain disorders and by our previous report in which we demonstrated that PDE7 inhibition after S14 treatment in vivo induces a strong neurogenesis in the substantia nigra pars compacta of 6‐OHDA‐lesioned animals toward a dopaminergic phenotype .…”
Section: Discussionsupporting
confidence: 77%
“…Although our group has recently demonstrated that PDE7 inhibition plays an important role on neuroprotection in different animal models of neurodegenerative disorders , so far there is almost no information about the effect of PDE7 inhibition on neurogenesis in the adult brain. More recently, our group has reported for the first time that the PDE7 inhibitor S14, which is able to cross the blood brain barrier, induces neurogenesis toward a dopaminergic phenotype in the substantia nigra pars compacta of adult rats lesioned with 6‐OHDA .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PDE inhibition has been previously discussed as therapeutic approach for Huntington’s disease 37 and Alzheimer’s disease 38 . It was also reported that inhibition of the cAMP-selective PDE7 protected dopaminergic neurons in a 6-hydroxydopamine model of PD in vivo 39 . Moreover, PDE1 inhibition was discussed as an approach to improve neuronal plasticity and to be neuroprotective as treatment option for neurodegenerative diseases 40 .…”
Section: Discussionmentioning
confidence: 92%